OUTCROP EXPLORER: A POINT-BASED SYSTEM FOR VISUALIZATION AND INTERPRETATION OF LiDAR DIGITAL MODELS - Bellina, Gabriel Marx; Tognoli, Francisco Manoel Wohnrath; Veronez, Mauricio Roberto (Revista Brasileira de Cartografia, 2018)
The use of LiDAR-based models for natural outcrops and surfaces studies has increased in the last few years. This technique has been found to be potential to represent digitally tridimensional data, thus it increases the quality and amount of data available for interpretation by geoscientists. Researchers, in computations, face difficulties in handling the huge amount of the data acquired by LiDAR systems. It is difficult to visualize efficiently the point cloud and convert it to high-quality digital models (DMs) with specific interpretation tools. Some in-house and commercial software solutions have been developed by some research groups and industries, respectively. However, all solutions must consider the large database as the pain point of the project. Outcrop Explorer has been developed to manage large point clouds, to provide interpretation tools, and to allow integration with other applications through data exporting. In terms of software architecture, view-dependent level of detail (LOD) and a hierarchical space-partitioning structure in the form of octree are integrated in order to optimize the data access and to promote a proper visualization and navigation in the DM. This paper presents a system developed for visualization, handling and interpretation of digital models obtained from point clouds of LiDAR surveys. This system was developed considering the free graphic resources, the necessities of the geoscientists and the limitations of the commercial tools for interpretation purposes. It provides an editing tool to remove noise or unnecessary portions of the point cloud and interpretation tools to identify lines and planes, as well as their orientations, and it has different exporting formats. However, being an open source project much more collaborative development is necessary.